A contribution to the Slovenian spider fauna – IV - Žan Kuralt; Rok Kostanjšek (Natura Sloveniae)
We provide a list of 171 spider species from 27 families recently recorded in Slovenia. Among them are first records of Nigma flavescens, Walckenaria alticeps, Pelecopsis parallela, Erigone autumnalis and Micaria subopaca for Slovenia and a second record of Zodarion rubidum, a species just recently added to the Slovenian spider fauna.